Fashion & Luxury Marketing - Solomon, Michael R. (SAGE Publications, Ltd. (UK), 2022)
Written by marketing experts, this authoritative and comprehensive full-colour textbook made up of both accessible research and theory, real-world examples and case studies including Prada, Gucci and Burberry, provides students with an overview of the global fashion industry and fashion marketing, strategy, branding, communications, retailing and distribution, as well as the psychological factors involved in consuming fashion and luxury. The role of social media, celebrities and influencers such as Kim Kardashian and Lil Miquela are discussed, as is the ever-increasing role of ethical fashion and sustainability. The authors also offer an expanded view of fashion and luxury by moving beyond just clothing and apparel to include other fashionable and luxurious products and services, including technology.   Packed with attractive visuals from fashion and culture, and accompanied by chapter summaries, questions and exercises, this textbook is essential reading for students studying fashion, luxury, marketing, management, retailing, branding and communications. Also provided for educators are supporting PowerPoint slides and an instructor’s manual to support use of the textbook with students. Suitable for Fashion Marketing/Fashion Consumer Behaviour modules as well as a general text for Fashion Marketing programmes. The text will also appeal to Luxury programmes (MBA etc) and Retail Marketing modules (UG).